WORLD TRAINING SAILING BOATS - Yeroshkina , S.G. (The actual problems of regional economy development, 2016)
In scientific article is researched tendencies, which took place in historical process of the world segmentation of sailing tall ships and their influence on modern composition on whole word’s training sailing boats. By variety parameters modern composition of ships was done the estimation of most biggest tall sailing ships. Complete technical description of the powerful sailing tall ships was done on the present day. Identified and given the technical possibilities for further exploitation of Ukrainian training sailing boats. Assesses the current state of the sailing fleet in terms of economic costs and expenses of Crimea’s occupation and continuous war on eastern region of Ukraine. JEL: L 92